Life at Interfaces and Under Extreme Conditions Proceedings of the 33rd European Marine Biology Symposium, held at Wilhelmshaven, Germany, 7–11 September 1998 - Liebezeit, Gerd; Dittmann, Sabine; Kröncke, Ingrid (Developments in Hydrobiology, 2000)
Interfaces between media, whether air-water or sediment-water interfaces or organisms themselves, pose considerable problems to marine organisms attempting to live at these boundaries. In the present volume, a number of authors address various aspects of these two topics. Locations under scrutiny range from intertidal areas to the deep sea, while both macro-and meiofaunal organisms are investigated. Distribution patterns and effects of variable temperatures, pressures, and salinities are analysed. Aspects of fouling induction and prevention are also addressed. This book is intended as a progress report from the 33rd European Marine Biology Symposium held in Wilhelmshaven, Germany, in September 1998